Potential impact of a nonavalent HPV vaccine on HPV related low-and high-grade cervical intraepithelial lesions: A referral hospital-based study in Sicily. Issue 8 (3rd August 2017) - Capra, Giuseppina; Giovannelli, Lucia; Matranga, Domenica; Bellavia, Carmelina; Guarneri, Maria Francesca; Fasciana, Teresa; Scaduto, Giovanna; Firenze, Alberto; Vassiliadis, Alessandra; Perino, Antonio
ABSTRACT: While bivalent and quadrivalent HPV vaccines have been used for about 10 years, a nonavalent vaccine against HPV types 6/11/16/18/31/33/45/52 and 58 has been recently approved by FDA and EMA and is now commercially available. The objective of our study was to evaluate the potential impact of the nonavalent vaccine on HPV infection and related low- and high-grade squamous intraepithelial lesions (LSIL, HSIL), compared to the impact of the quadrivalent vaccine, in a female population living in Sicily (Italy). Low estimates of HPV vaccine impact were calculated as prevalence of HPV 6/11/16/18/31/33/45/52 and 58 genotypes, alone or in association, but excluding presence of other HPV types; high estimates were calculated as prevalence of HPV 6/11/16/18/31/33/45/52 and 58 genotypes alone or in association, in the presence of other HPV types. The nonavalent HPV vaccine showed increased impact, compared to the quadrivalent vaccine. Estimates of potential impact varied from 30.9% (low estimate) to 53.3% (high estimate) for LSIL, and from 56.9% to 81, 0% for HSIL. The proportion of additional cases potentially prevented by the nonavalent vaccine was 14.4%–23.8% for LSIL, and 19.0%–32.8% for HSIL. The benefit of the nonavalent vaccine compared to the quadrivalent vaccine was more than 80% for both low and high impact estimates for LSIL and more than 50% for both low and high impact estimates for HSIL. The present study confirms that the switch from a first generation HPV vaccines to a nonavalent vaccine would increase the prevention of cervical HSIL in up to 90% of cases.